EMD: entity mapping diagram for automated extraction, transformation, and loading processes in data warehousing. (1st January 2012) - Hendawi, Abdeltawab M.A.; Ali El-Sappagh, Shaker H.
During the last few years, researchers and developers had proposed various trials to put a standard conceptual design of ETL processes in data warehouse. These trials try to represent the main mapping activities at the conceptual level. Due to limitations of the previous trials, in this paper 1 We propose a model for conceptual design of ETL processes and we call it entity mapping diagram (EMD). The proposed model is built upon the enhancement of the models in the previous work to support some missing mapping features. 2 We implemented the proposed conceptual model in a prototype called EMD Builder and use it in an illustration scenario.